Relationship between Perceived Factors for Effective Logistics and Customer Satisfaction: A Case of Tanzania’s Telecommunication Industry - Tusiime, Wilson; Ahimbisibwe, Arthur; Nangoli, Sudi (ORSEA JOURNAL, 2018)
In recent years, the Tanzania’s telecommunication industry has been seen as one of the most evolving industries in the country due to dynamic technological changes leading to increased levels of competition, thereby forcing customers to constantly switch to different companies though there are numerous logistical services provided by the companies. This research investigates the relationship between the perceived factors for effective logistics and customer satisfaction in Tanzania’s telecommunication industry. Case study design methodology was used whereby primary data were obtained through observation, in-depth and documentary review. Findings revealed a coefficient correlation of 0.625, thus, it was concluded that there is a strong relationship between perceived factors for effective logistics and customer satisfaction. It is recommended that for telecommunication companies to effectively serve their customers and survive in this highly competitive market, there is need for the telecom companies to put a lot of emphasis on perceived factors for effective logistics. Managerial and theoretical implications are also well discussed in this article.
Keywords: Perceived Factors; Effective Logistics; Customer Satisfaction; Tanzania’s Telecommunication Industry